A epistemologia naturalizada de Quine - Bruno Batista Pettersen (2006)
The subject of this dissertation is Willard Quines Naturalized Epistemology. In the first chapter, we investigate its origins within the tradition of empiricism. We examine David Humes naturalistic theory of belief and Rudolf Carnaps reductionistic agenda for the philosophy of science. Quines epistemology emerges from the criticism of those positions. The second chapter is a close examination of Quines classic paper "Epistemology Naturalized" (1969). We begin by a presentation of the criticism of the concept of "empirical meaning", and then show how this criticism leads Quine to his own version of an empiricist epistemology. His naturalized epistemology has two main tenets, both reformulated from the tradition: (1) naturalism - epistemology becomes a chapter of the natural sciences, such as psychology - and (2) a version of empiricism in which the verification of a sentence or a theory can only be made in a holistic mode. The third chapter is concerned with the criticisms of Quines project. We present four criticisms; two closer to Quine, by Jaegwon Kim and Donald Davidson, and two from a more distant point of view, by Laurence Bonjour and Barry Stroud. At the end of this chapter we suggest quinean responses to those criticisms.